Experimental validation of a flat punch indentation methodology calibrated against unconfined compression tests for determination of soft tissue biomechanics. (July 2016) - Delaine-Smith, R.M.; Burney, S.; Balkwill, F.R.; Knight, M.M.
Abstract: Mechanical characterisation of soft biological tissues using standard compression or tensile testing presents a significant challenge due to specimen geometrical irregularities, difficulties in cutting intact and appropriately sized test samples, and issues with slippage or damage at the grips. Indentation can overcome these problems but requires fitting a model to the resulting load–displacement data in order to calculate moduli. Despite the widespread use of this technique, few studies experimentally validate their chosen model or compensate for boundary effects. In this study, viscoelastic hydrogels of different concentrations and dimensions were used to calibrate an indentation technique performed at large specimen-strain deformation (20%) and analysed with a range of routinely used mathematical models. A rigid, flat-ended cylindrical indenter was applied to each specimen from which 'indentation moduli' and relaxation properties were calculated and compared against values obtained from unconfined compression. Only one indentation model showed good agreement (<10% difference) with all moduli values obtained from compression. A sample thickness to indenter diameter ratio ≥1:1 and sample diameter to indenter diameter ratio ≥4:1 was necessary to achieve the greatest accuracy. However, it is not always possible to use biological samples within these limits, therefore we developed a series of correction factors. The approach was validated using human diseased omentum and bovine articular cartilage resulting in mechanical properties closely matching compression values. We therefore present a widely useable indentation analysis method to allow more accurate calculation of material mechanics which is important in the study of soft tissue development, ageing, health and disease. Graphical abstract: Highlights: Experimental calibration: indentation versus compression of soft viscoelastic gels. Simple mathematical indentation models tested for accuracy at large strain (20%). We generate correction factors accounting for model errors and specimen geometry. Corrected models validated against soft biological tissues; omentum and cartilage. Correction factors can be applied to soft materials in the range 0.001–10 MPa.